Experience Marketing: Strategies for the New Millenium - O'Sullivan, Ellen Lupia; Spangler, Kathy J. (Venture Pub., 1998)
Keywords: Marketing; Marketing; Leisure; Marketing; Recreation; Parks; dept.pch; faculty_collection

Correlates of sexual satisfaction in marriage - Young, M; Denny, George; Luquis, Raffy; Young, Tamera (Canadian Journal of Human Sexuality, 1998)
Hypotheses concerning possible correlates of sexual satisfaction in marriage were tested using the replies of 797 married women and men of diverse ages to a 70-item mailed questionnaire that contained seven Likert-type sub-scales measuring different sexual and non-sexual variables. Multiple regression analysis, using sexual satisfaction as the dependent variable, yielded a five-variable model that accounted for a significant portion of the variation in sexual satisfaction (Adjusted R Squared = .602). The variable 'overall satisfaction with marriage' had the highest correlation with sexual satisfaction (r = .622), followed by 'satisfaction with non-sexual aspects of the relationship' (r = .609), frequency of spouse/partner orgasm per sexual encounter (r = .529), frequency of sexual activity (r = .370), and 'sexual uninhibitedness' (r = .230). None of three measures of religiosity made a significant contribution to explaining the variation on self reported sexual satisfaction. Men and women did not differ in level of sexual satisfaction, and adding gender to the regression model did not increase the level of explained variation. The results indicate that sexual satisfaction in these married respondents could not be compartmentalized to their sexual interactions, but was strongly associated with non-sexual aspects of the overall marital relationship as well.
Citation Key Alias: lens.org/095-547-782-487-373 tex.type: [object Object]
Keywords: Marital satisfaction; Relationship satisfaction; Religiosity; Sexual satisfaction; Spouse-partner orgasm consistency; aged; article; dept.pch; female; human; male; marriage; multiple regression; normal human; orgasm; questionnaire; religion; satisfaction; sexual behavior; ⛔ No DOI found